Public Interest in Acne on the Internet: Comparison of Search Information From Google Trends and Naver - Park, Tae Heum (J Med Internet Res, 2020)
BACKGROUND: Acne vulgaris is a common skin disease primarily affecting young adults. Given that the internet has become a major source of health information, especially among the young, the internet is a powerful tool of communication and has a significant influence on patients. OBJECTIVE: This study aimed to clarify the features of patients’ interest in and evaluate the quality of information about acne vulgaris on the internet. METHODS: We compared the search volumes on acne vulgaris with those of other dermatological diseases using Google Trends from January 2004 to August 2019. We also determined the search volumes for relevant keywords of acne vulgaris on Google and Naver and evaluated the quality of answers to the queries in KnowledgeiN. RESULTS: The regression analysis of Google Trends data demonstrated that the patients’ interest in acne vulgaris was higher than that for other dermatological diseases, such as atopic dermatitis (β=−20.33, 95% CI –22.27 to –18.39, P<.001) and urticaria (β=−27.09, 95% CI –29.03 to –25.15, P<.001) and has increased yearly (β=2.38, 95% CI 2.05 to 2.71, P<.001). The search volume for acne vulgaris was significantly higher in the summer than in the spring (β=–5.04, 95% CI –9.21 to –0.88, P=.018) and on weekends than on weekdays (β=–6.68, 95% CI –13.18 to –0.18, P=.044). The most frequently searched relevant keywords with “acne vulgaris” and “cause” were “stress,” “food,” and “cosmetics.” Among food, the 2 highest acne vulgaris–related keywords were milk and wheat in Naver and coffee and ramen in Google. The queries in Naver KnowledgeiN were mostly answered by a Korean traditional medicine doctor (53.4%) or the public (33.6%), but only 12.0% by dermatologists. CONCLUSIONS: Physicians should be aware of patients’ interest in and beliefs about acne vulgaris to provide the best patient education and care, both online and in the clinic.